Caminhos do intermezzo: as relações Mebêngôkre (Kayapó) na cidade de Ourilândia do Norte - PA - Amorim, Marcelly Olivia Fernandes (2020)
The present work seeks to reflect on the institutional, social and cultural dynamics that permeate the activities of the Mebêngôkre (Kayapós) in the city of Ourilândia do Norte, located in southeastern Pará. We intend to specifically address the process of displacement of these people to the city, about the Mebêngôkre point of view. The displacement of the Mebêngôkre (Kayapós) between the village and the city mobilizes elements of an institutional practical nature that relates various agents and objects, systematically identified with multiple intentions and that directly interfere in the subjectivation processes of the group, that is, allows the incorporation of new ones. cultural cadences, perspectives of symbolic appropriation and the predation of the other, categories that make up the cosmology of the Jê and Macro-Jê peoples. To this end, we use the bibliographic analysis of important anthropological authors who approach the Mebêngôkre ethnic group, aiming to break with dualities, starting from the opening to multiplicities. As well as the ethnographic work that took place in the city of Ourilândia do Norte, by accompanying people from the Mebêngôkre (Kayapó) ethnic group, who were, at first, temporarily in the City, in order to experience the Mebêngôkre vision of this process.